Development of Android-Based Digital Drawing Learning Media Using Online Applications - Hendriyanto, Novi; Rokhman, Nur (Edukasi, 2021)
The existence of COVID-19 has caused many problems in various fields, one of which is the world of education. Students are required to study remotely so that there is a need for innovation in learning media so that learning materials can still be accepted by students. The purpose of this research is to create digital image learning media as a support for illustration courses in animation study programs where digital drawing skills are needed. The learning media is packaged in an Android-based application to make it easier for students to access because Android is currently often used by students. The method used in building this application is the waterfall method. As for the software needed to build this application, it uses Google sites technology, appsgeyser for navigation and content and Adobe Photopea for design. The result of this research is the creation of digital image learning media applications as a support for illustration courses that can be accessed easily by students. At this stage of testing this application using the black box method to test the program's functionality and also conduct a feasibility test. For the test results, all features can function properly and for the feasibility value, it gets a score of 87% or falls into the very feasible category.